PATU1 Characteristic faciobrachial dystonic seizures as an immunotherapy-responsive prodrome to voltage-gated potassium channel antibody-associated limbic encephalitis. Issue 11 (22nd October 2010) - Irani, S; Michell, A W; Lang, B; Vincent, A; Sommerville, E R; Johnson, M R; Smith, S M J
Abstract : LE defines the subacute onset of amnesia and seizures. However, there are few reliable clinical features distinguishing VGKC-antibody associated LE from the many other forms of LE. Identification of such features may aid early diagnosis and immunotherapy administration. We describe 26 patients with median age at onset of 64.5 years (36–73) who developed characteristic, brief (few seconds), frequent (mean of 65 per day) dystonic seizures involving the arm (in 100%) and face (in 73%). All patients had high VGKC-antibody levels (mean 2403 pM, 238–6129; normal values <100 pM). Interestingly, in the majority (77%), with a median lag of 29 days (2–850), these seizures preceded a typical VGKC-antibody associated LE. No patients had malignancies detected (median follow-up 2.75 years (0.5–8)). Only 19% showed a reduction in seizure frequency on anti-epileptic therapy and 46% developed (often severe) side-effects. By contrast, 81% responded well to various immunotherapies: these clinical improvements correlated well with immunotherapy-induced reductions in VGKC-Abs in individual cases. These characteristic dystonic seizures occurring in later life herald the onset of VGKC-antibody associated nonparaneoplastic limbic encephalitis. Their recognition should lead to increased awareness of the syndrome and prompt immunotherapy.